Plant species used in animal feeding in Mera, Santa Clara and Pastaza cantons in Pastaza province, Ecuador - Abril, R. V.; Aguinda, Janeth K.; Ruiz, Tomás E.; Alonso, Jatnel (Cuban Journal of Agricultural Science, 2016)
This study was developed in Mera, Santa Clara and Pastaza cantons, located in Pastaza province, Ecuador, to identify accessions used by agricultural producers in animal feeding and to know its performance, in function of the use frequency, related to the canton, ethnicity of the producer, main source of economical incomes, type of farm production, years of experience, and other types of uses. A survey was applied to 214 producers, for 30% of the founded in their farms. Socioeconomic aspects, ecosystem description of the place and use of the plants in their farms were considered. Samples of the species used in animal feeding were collected and they were transported to the Amazon State University herbarium. The analysis of the results by means of the proportions square application, in function of the report frequency of each species, showed chi square of Pearson significance differences in the canton component, ethnicity of the producer, main source of economical incomes, and other type of species use. The analysis of report frequencies, applying Duncan test, stated that the species Axonopus scoparius, Bactris gasipaes, Bracharia brizanta, Colocasia sculenta, Cymbopogon citratus, Manhiot sculenta, Musa sp., Penisetum purpureum, Pouteria caimito, Psidium guajava, Saccharum officinarum L. and Zea mayz, showed different performances, while Axonopus scoparius showed differences in higher number of analysis. It is concluded that the geographical, cultural and economical factors, influence in the use report frequency, having in several species, animal feeding as alternative to other established uses. Key words: animal feeding, distribution, ethnicity